A review on bio-fertilizer and the benefits of using bio-fertilizer towards oil palm plantation / Muhammad Thalhah Rosli - Rosli, Muhammad Thalhah (Faculty of Plantation and Agrotechnology, 2018)
Oil palm plantation is one of the main commodities in South East Asia especially in Malaysia and Indonesia. However, because of the increasing in the price of chemical fertilizer, number of efforts have been done in order to minimize cost and elevate the efficiency in chemical fertilizer application at oil palm plantations by introducing the use of bio-fertilizer. This fertilizer is a substance that consists of living organism that is introduced to the soil to promote growth by enhancing the availability of essential primary nutrients to the plant. Bio-fertilizer is well-known for their eco-friendly nature. The inclusion of nutrients into the soil is done by natural processes such as fixation of nitogen, solubilization of phosphorus, and increase plant stimulation through the production of growth-promoting substances. Bio-fertilizers are also made up of several different sources such microbes for the interaction with the plant. Other substances can also be used in producing bio-fertilizer such as EFB that is used as a carrier for Trichoderma spp. Bio-fertilizers comprise of many advantages as it is environmental friendly and more cost-effective as compared to the chemical fertilizer.